Aggregation by Industry in General Equilibrium Models with International Trade - Lloyd, Peter J.. (OECD Development Centre Working Papers, 1991)
Models of trading economies have become very large in dimensions and complex in structure. This paper seeks conditions under which it is possible to aggregate the production and consumption of groups of commodities in "industries": commodity groups sharing some common characteristics and behaviour. The most extreme form of aggregation is the simultaneous aggregation of the same commodities using the same aggregator functions on both the production and consumption sides of the model. This is called "complete aggregation". If this can be done, the competitive equilibrium can be determined in two stages and the commodity dimensions of a model can be reduced drastically, perhaps to very few. In other cases it is possible to aggregate commodities only on the production or the consumption side of the model. Such aggregation will simplify the production or consumption side and allow the derivation of new results. Conditions which are sufficient for aggregation in production or ...